The introduced oak Quercus rubra and acorn‐associated arthropods in Europe: An opportunity for both carpophagous insects and their ant predators. (17th February 2022) - Giannetti, Daniele; Schifani, Enrico; Castracani, Cristina; Spotti, Fiorenza Augusta; Mori, Alessandra; Grasso, Donato Antonio
Abstract: We studied the interactions involving oak acorns and associated arthropods focusing on the role of the introduced Quercus rubra in Italy. We conducted our study in areas where native oaks coexist with Q. rubra . We carried out a survey on the arthropods inhabiting fallen acorns and a colonisation experiment. Furthermore, we conducted laboratory experiments documenting the interactions among the most abundant arthropod species on Q. rubra . Acorns were colonised by ant species and carpophagous insects showing different preferences concerning acorns' position within the leaf litter and oak species. Acorns of Q. rubra were colonised frequently by ants (mostly Temnothorax nylanderi ) and Cydia fagiglandana . Cydia splendana preferred native acorns, while Curculio beetles were ubiquitous. Our data suggest that ants occupy exclusively acorns previously attacked by Cydia, killing or displacing their caterpillars if still developing inside the acorns. Vertebrates may prefer to feed on Q. rubra acorns over native species. Quercus rubra has a meaningful influence on native arthropods associated with oak acorns. The ecological consequences of this interaction are still not fully clear, yet our data suggest an increase in acorn‐consuming insects, partly affecting the acorns of neighbouring native oaks, but also an increase of predatory ants. Abstract : Quercus rubra is an introduced oak species in Europe. Its effect on the acorn‐associated arthropod fauna is still little‐known. We investigated it in Italy, documenting novel interactions between acorn‐colonizers. Carpophagous insects ( Cydia spp., Curculio spp.) and ants were the main acorn‐colonizing species, showing different preferences between native and Q. rubra acorns and different positions in the forest litter. Ants nested in acorns previously consumed by moths or killed/displaced the caterpillars if they met them. Ants and their preys were more abundant in the presence of Q. rubra .